Faktor penentu tahap kepuasan pengguna terhadap “stamp assessment and payment system” (stamps) di Muar, Johor - Siti Aisyah, Muhamad (2022)
The world was affected by the disaster of the Covid-19 disease epidemic that began at the end of year 2019. This consequence led to the closure of private and government premises and the implementation of online services became an alternative way instead of existing face-to-face services. In order to speed up the current of digitization and faced the challenges of Covid-19 pandemic Inland Revenue Board of Malaysia (IRBM) replaced the manual Digital Franking System to Stamp Assessment and Payment System (STAMPS), especially for agents and companies where it is carried out entirely online. This study was conducted to identify the level of user satisfaction of the STAMPS system in Muar District. This research also examines the determining factors and their correlation toward user satisfaction of the STAMPS system in Muar District. A total of 100 external and internal user respondents were involved in this research, consisting of STAMPS agents from law firms and IRBM officers. Three quality of e- Service model was applied to determine the factors that contribute to the level of user satisfaction of the STAMPS system. The analysis was carried out descriptively, regression and correlation and the results of this research found that users of the STAMPS system have rated a high level of satisfaction after using this system. Findings of regression analysis, the factors of web design and efficiency are the biggest contributors to the level of user satisfaction of STAMPS in Muar district. Two factors which are web design and information have a strong correlation with the assessment of user satisfaction. While factors of efficiency, system availability, responsive and ease of use show a moderate relationship with the assessment of user satisfaction. The privacy factor shows a weak relationship strength with user satisfaction ratings. Any good and service marketed or used by the community must be evaluated to find the level of user satisfaction after using it. The high level of customer satisfaction achieved by IRBM Muar through STAMPS is an indicator and appreciation for the organization and it becomes a benchmark demonstrated IRBM is on the right path in achieving the objectives of system development. The contribution of STAMPS which became a new platform in continuing services during the infectious epidemic can be proven by the increase in the collection of stamp duty against Malaysia's direct taxes in 2021.